PENGARUH SIKAP KERJA, KEMAMPUAN DIRI DAN STRES KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DAERAH KOTA PADANGSIDIMPUAN - Syawan Sani Siregar; Andi Zuanda; Muhammad Kholidin Hasibuan; Afrianny .; Desviani Yulinda Yusuf (Universitas Islam Islam Sumatera Utara, 2020)
Problem of this study is how influence of job attitude on employee’s performance. How influence of self ability on employee’s performance. How influence of job stress on employee’s performance. How influence job attitude, self ability and self ability on employee’s performance. The purpose of this study to determine and analyze the effect of job attitude on employee’s performance. Determine and analyze the effect of self ability on employee’s performance. Determine and analyze the effect of job stress on employee’s performance. Determine and analyze the effect job attitude, self ability and job stress on employee’s performance. Sample in the study is 52 people. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job attitude variable has a positive and significant effect on employee’s performance. Self ability variable has a positive and significant effect on employee’s performance. Job stress variable has a positive and significant effect on employee’s performance. Job attitude, self ability and job stress variable has a positive and significant effect on employee’s performance.